Santonian–Campanian (Late Cretaceous) planktonic foraminiferal turnover, depth ecology and paleoceanographic implications - F. Falzoni; M.R. Petrizzo; B. T. Huber; K. G. MacLeod (2013)
The Santonian–Campanian time interval is a transitional phase from the extreme greenhouse warmth during the Turonian to more temperate conditions and to a thermohaline circulation that was more like that of the modern day. These environmental changes led to a re-organization of marine ecosystems in deep-sea and superficial settings and to the formation of well-developed faunal bioprovinces that were analogous to the present. This environmental instability likely led to a major faunal turnover among planktonic foraminifera including extinction of the genera Marginotruncana and Dicarinella and diversification within the genera Globotruncana, Globotruncanita and Contusotruncana (Premoli Silva and Sliter, 1999). Relatively few studies on the composition of Santonian-Campanian planktonic foraminiferal assemblages are available in the literature, and those have never been coupled with reliable species-specific stable isotope (δ13C and δ18O) analyses, mainly because: (1) DSDP (Deep See Drilling Project), ODP (Ocean Drilling Program) and IODP (Integrated Ocean Drilling Program) cruises recovered relatively few and discontinuous stratigraphic sequences belonging to this interval, and (2) planktonic foraminifera from deep-sea sites are often diagenetically altered and do not yield reliable isotopic records of paleoenvironmental condtions. The unusual recovery of pristinely preserved planktonic foraminifera from Santonian–Campanian sequences in southeastern Tanzania (Tanzania Drilling Project, TDP Sites 28 and 32, see Jiménez Berrocoso et al., 2012), allowed examination of faunal changes and well resolved, species-specific stable isotope (δ13C and δ18O) data. These data are ideal for inferring paleoecological preferences of different species and for tracing major paleoceanographic changes. Results obtained from TDP material have been compared with δ13C and δ18O values inferred from specimens recovered at two low-to-mid latitude sites (1) Shatsky Rise (ODP Leg 198, Hole 1210B; northwestern Pacific Ocean) and (2) Exmouth ...